(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The utilization of mobile applications and services by the smartphone users is ever increasing over the last two decades. A considerable amount of research work has been done in this field with different aims and objectives. The aim of the work done in this study is to understand the preferences of smartphone users regarding the usage of the Internet in their devices either by mobile applications or via mobile websites. Our findings will be useful for mobile application developers to understand the main aspects of consumers and what they expect from their mobile usage experience. The study was conducted in two phases. In the first phase, a survey was conducted with over 250 participants. In the second phase, interviews were conducted with 30 participants based on testing two implemented applications (a native mobile application and a mobile website). The collected data is analyzed using different statistical methods. Obtained results show that mobile applications are mostly preferred, especially for the most common and frequently used applications among users. Moreover, respondents find that mobile applications are better in most aspects. However, we cannot ignore the proportion of participants who make their preferences according to site.